The Beneficial Effect of HES on Vascular Permeability and Its Relationship With Endothelial Glycocalyx and Intercellular Junction After Hemorrhagic Shock - Zhao, Hongliang; Zhu, Yu; Zhang, Jie; Wu, Yue; Xiang, Xinming; Zhang, Zisen; Li, Tao; Liu, Liangming (Frontiers in Pharmacology, 2020)
Background: Vascular leakage is a common complication of hemorrhagic shock. Endothelial glycocalyx plays a crucial role in the protection of vascular endothelial barrier function. Hydroxyethyl starch (HES) is a commonly used resuscitation fluid for hemorrhagic shock. However, whether the protective effect of HES on vascular permeability after hemorrhagic shock is associated with the endothelial glycocalyx is unclear. Methods: Using hemorrhagic shock rat model and hypoxia treated vascular endothelial cells (VECs), effects of HES (130/0.4) on pulmonary vascular permeability and the relationship to endothelial glycocalyx were observed. Results: Pulmonary vascular permeability was significantly increased after hemorrhagic shock, as evidenced by the increased permeability of pulmonary vessels to albumin-fluorescein isothiocyanate conjugate (FITC-BSA) and Evans blue, the decreased transendothelial electrical resistance of VECs and the increased transmittance of FITC-BSA . The structure of the endothelial glycocalyx was destroyed, showing a decrease in thickness. The expression of heparan sulfate, hyaluronic acid, and chondroitin sulfate, the components of the endothelial glycocalyx, was significantly decreased. HES (130/0.4) significantly improved the vascular barrier function, recovered the thickness and the expression of components of the endothelial glycocalyx by down-regulating the expression of heparinase, hyaluronidase, and neuraminidase, and meanwhile increased the expression of intercellular junction proteins ZO-1, occludin, and VE-cadherin. Degradation of endothelial glycocalyx with degrading enzyme (heparinase, hyaluronidase, and neuraminidase) abolished the beneficial effect of HES on vascular permeability, but had no significant effect on the recovery of the expression of endothelial intercellular junction proteins induced by HES (130/0.4). HES (130/0.4) decreased the expression of cleaved-caspase-3 induced by hemorrhagic shock. Conclusions: HES (130/0.4) has protective effect on vascular barrier function after hemorrgic shock.The mechanism is mainly related to the protective effect of HES on endothelial glycocalyx and intercellular junction proteins. The protective effect of HES on endothelial glycocalyx was associated with the down-regulated expression of heparinase, hyaluronidase, and neuraminidase. HES (130/0.4) had an anti-apoptotic effect in hemorrhagic shock.